Impact of lipid oxidization on biophysical properties of model cell membranes - Makky, Ali; Tanaka, Motomu (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2015)
The oxidization of glycerophospholipids in cell membranes due to aging and environmental stresses may cause a variety of pathological and physiological consequences. A variety of oxidized phospholipid products (OxPl) are produced by the chemical oxidization of unsaturated hydrocarbon chains, which would significantly change the physicochemical properties of cell membranes. In this work, we constructed cell membrane models in the absence and presence of two stable oxidized lipid products and investigated their impact on physical properties of supported membranes using quartz crystal microbalance with dissipation (QCM-D) and high-energy X-ray reflectivity (XRR). Our experimental findings suggest that the lipid oxidization up to 20 mol % leads to the rupture of vesicles right after the adsorption. Our XRR analysis unravels the membrane thinning and the decrease in the lateral ordering of lipids, which can be explained by the decrease in the lateral packing of hydrocarbon chains. Further studies on mechanics of membranes incorporating oxidized lipids can be attributed to the decrease in the bending rigidity and the increase in the permeability.